Suprapubic Catheter in a Patient with Bladder Carcinoma, Against the Prohibition: A Systematic Review and Case Report - Derri Hafa Nurfajri; Sawkar Vijay Pramod; Ferry Safriadi; Betty Suryawathy Hernowo (Asian Pacific Journal of Cancer Care, 2022)
Background: Bladder tumors are the most common neoplasm of the lower urinary tract. Bladder carcinoma arising from a suprapubic cystostomy tract is a relatively rare. Some patients with bladder tumors have difficult urethral access for urinary retention due to inaccessible urethra. Most people think cystostomy in patient with bladder cancer can cause seeding and upstaging to suprapubic cystostomy tract. This study aim of suprapubic cystostomy can cause seeding and upstaging of bladder cancer. Methods: Literature obtained from the search results of Pubmed, Medscape, Science Direct, Scopus, Cochrane Library, and Google Scholar electronic databases with the keywords used are “suprapubic catheter and bladder cancer”, “suprapubic catheter and bladder tumor”, “suprapubic catheter and bladder carcinoma”, “suprapubic cystotomy and bladder carcinoma”, and “suprapubic catheter and bladder cancer upstaging” with no time limits. Results: Eighty two articles were obtained from the electronic database. Following all the inclusion and exclusion criteria, the final selection considered 5 literature with 16 patient eligible for this literature review. The five literature involved a total of 16 bladder cancer patients with a suprapubic catheter. The duration of suprapubic catheter insertion was between 1 to 3 months. As long as it is within the specified time and from the location of cancer, literature result there will be no seeding and upgrading in the suprapubic cystostomy tract. In our case report we have patient with duration suprapubic cystostomy 1 months wih no seeding and upgrading cancer. Conclusion: Although SPC is an effective, inexpensive, easy mode of access for bladder tumors with difficult urethral access for urinary retention due to inaccessible urethra, it also presents a risk of SPC tract bladder cancer, mostly SCC and TCC. It is important to be aware of any suspicious signs and symptoms, duration time of use suprapubic cystostomy and location of the cancer.